Reproductive histology of three species of Polyplacophora (Mollusca) from Waikiki and La Pampilla beaches, Lima, Peru - Dávila-Robles, Miguel (2024)
The “Chitons” are marine inhabitants that are geographically distributed from Ecuador to Chile. Their value as bioindicators and biological controllers is highlighted since they feed on algae and colonial animals. This study aims to describe the gonadal histology of females and males of Chiton granosus (Frembly, 1827), Enoplochiton niger (Barnes, 1824), and Acanthopleura echinata (Barnes, 1824) by recognizing oogenesis and spermatogenesis. The gonad was extracted from five individuals for each species by dissecting the dorsal area of the body and the Histological Technique with Hematoxylin- Eosin (H-E) staining was applied. The common structures identified in females and males are germ tissue and gonadal wall. About oogenesis, the following were observed: oogonia, in contact with the germ tissue; previtellogenic oocytes with a highly vacuolated or granulous cytoplasm presenting an acidophilic stain and the vitellogenic oocytes arranged towards the lumen of the gonad. On the other hand, in spermatogenesis, spermatogonia are spherical and arranged in germ tissue; primary spermatocytes, are amorphous; Secondary spermatocytes and spermatids are grouped and far from the germinal tissue. Finally, the sperm were located in the lumen of the gonad while maintaining the triangular shape and a developed tail. In conclusion, in the three species of chitons, it was identified the five cellular phases of oogenesis and spermatogenesis, due to the shape, size, and characteristic coloration of each cell group.